THE IMPLEMENTATION OF RSA ALGORITHM IN TEXT MESSAGES ENCRYPTION AND DECRYPTION - Mondal, Shovan; Primajaya, Aji (JATI (Jurnal Mahasiswa Teknik Informatika), 2024)
In terms of texting, especially in such an ultramodern period of time, precisely 4.0 Industry, one of its topmost challenge or problems faced is related to security. Thousands, if not, hundred thousands of crime are committed through text message hacking because text communication could contain plenitude of particular personal informations, similar as passwords, ID number, phone number, etc. Cryptography from the Discrete Mathematics field is one of the best option to cover the data contained in text messages, hence, as time passed by, it is developed into RSA Algorithm; encryption and decryption key. Anyone who possess the wrong key will still be able to get the message, but the encrypted version would be far different from the real one.. The conversation covers basic topics such the decryption process—which reverses this process using a private key—and the encryption process—which converts plaintext into ciphertext by means of a public key. using means of prime numbers in key generation using RSA, data confidentiality is facilitated, therefore allowing only those with the suitable private key to decode the messages. Different cases show how well RSA protects personal data sent across networks, therefore stressing its importance in enhancing safe digital communication. Using a public key, the encryption process transforms plaintext into ciphertext therefore only those with the corresponding private key can decode the message. RSA creates safe, asymmetric key pairs by means of a mathematical approach involving prime numbers, therefore impeding attackers' access into the system. Emphasizing RSA's relevance in maintaining communications safe in email, mobile, and online apps, practical examples show how effectively the algorithm performs for encrypting and decryption of text messages. The paper then discusses how difficult RSA computation is and emphasizes how much security is truly enhanced by employing big prime values. This paper emphasizes the need of RSA for safeguarding digital communications and establishing a safe environment for data flow in modern digital systems.